Celowość wdrażania i stosowania współczesnych koncepcji i metod zarządzania w małych przedsiębiorstwach - Lichtarski, Janusz Marek (Suitableness of Implementation of Modern Concepts and Methods of Management into the Practice of Small Enterprises, 2006)
There is a lot of modern concepts and methods of management, both in theory and practice. Most of them are dedicated to large enterprises and corporations. This raises a question about the suitableness of implementation of this kind of solutions into the practice of small firms. The specific of small enterprises causes that they may not need such solutions, because of simplicity and informal character of management system. In spite of presented doubts, it is possible and suitable to implement some elements of modern approaches, but the question concerns the directions of their modifications. The proposition is to make use of general principles in their present shape and make the tool kit shorter and more simply.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 86-95